Information Dissemination of Youth and Sustainable Development Goals - Henny Wirianata; Nicholas Richardson; Jonathan Sasmita (Faculty of Smart Technology and Engineering, Universitas Kristen Maranatha, Bandung, Indonesia, 2025)
The Sustainable Development Goals (SDGs) cannot be achieved without the active involvement of young people, who are one of the important pillars of sustainable development. They will be the ones who will experience the success or failure of the 2030 agenda of SDGs. Youth have great potential as agents of change who can create innovations. Therefore, it is important to foster self-awareness in youth of their important role in realizing sustainable development goals. A community service activity was carried out to provide a comprehensive understanding of the SDGs in Indonesia and encourage the active role of youth in realizing them. The event was in the form of information dissemination, conducted on Monday, September 9th, 2024, at 10:00 - 11:30. The event was delivered directly onsite at SMP Katolik Ricci 1. The event participants consisted of 9th-grade students who had been specially selected by the school to take part in the event. The learning method used in this community service activity is a combination of lecture and interactive discussion. To obtain comprehensive feedback, participants were asked to complete quizzes and questionnaires aimed at assessing the effectiveness of the activity as well as exploring participants' aspirations regarding their contribution to achieving SDGs. After attending this event, it can be concluded that students of SMP Katolik Ricci 1 gained knowledge about the role they can play as young people to support the achievement of SDGs in Indonesia and apply this knowledge in their daily lives.